IbM KELOMPOK USAHA BERSAMA (KUB) SULAM PITA DI KOTA SEMARANG - Fatmasari Sukesti; Triyono Triyono; Musdalifah Musdalifah; Alwiyah Alwiyah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The products of ribbon embroidery became a popular trend since five years ago. With the development of beautiful design and embroidered motifs, various embroidered ribbon products can be produced and become a promising business opportunity. Joint Business Group (KUB) "Tlogo Kreasi" and KUB "UripCollection" was established to address the economic problems of its members. Members of this business group consist of housewives who have sewing and embroidery skills. With these skills they set up a joint venture by producing various handmade embroidered ribbons of various bags, mukena, hoods, purses,household linen, and various wedding souvenirs. Unimus community service team with IbM program is conducting extension, training, practice and mentoring activities to product marketing together with joint business group (KUB) in order to implement one of the darma in Tridarma Perguruan Tinggi that is dedication to the community with the aim of increasing the knowledge and skills of the group business in the framework of product and business development as well as strengthening the group into a strong and independent business organization. Keywords: sulam pita, KUB "Tlogo Kreasi", KUB "Urip Collection"